PENGARUH KOMPETENSI, INDEPENDENSI, PENGALAMAN KERJA, KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH DAN REWARD SEBAGAI VARIABEL MODERATING - Laksana Hari, Bagus; Rasuli, M.; Darlis, Edfan (SOROT, 2015)
Abstract As an internal watchdog, Inspector auditors working in the government organization that the main task is to determine whether the policies and procedures established by top management (Regional Head) has been complied and went according to plan, determine whether or not the maintenance of the property, determine the efficiency and effectiveness of the procedure and government activities, in addition to the auditor is also required to have more skill in his duty to audit the quality of the resulting more perfect. This study examines all auditors who work in agencies in each district as Jambi province. With the number of samples taken are 168 people. By adding the expected reward as a moderating able to motivate the auditor to audit more produce good quality.